2017
DOI: 10.1007/s00415-017-8555-3
|View full text |Cite
|
Sign up to set email alerts
|

Lateralized microstructural changes in early-stage Parkinson’s disease in anterior olfactory structures, but not in substantia nigra

Abstract: Parkinson's disease (PD) is a progressive neurological disorder characterized by motor symptoms as well as severe deficits in olfactory function and microstructural changes in olfactory brain regions. Because of the evidence of asymmetric neuropathological features in early-stage PD, we examined whether lateralized microstructural changes occur in olfactory brain regions and the substantia nigra in a group of early-stage PD patients. Using diffusion tensor imaging (DTI) and the University of Pennsylvania Smell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 56 publications
2
12
0
Order By: Relevance
“…Using voxel-based analysis, two studies (90,148) found PD is associated with abnormal diffusivity in white matter tracts adjacent to the olfactory sulcus. Although tractography of the olfactory tract is practically difficult in this area, using ROI drawing, some studies (92,119,122) reported low FA of the olfactory tract in PD. Another interesting approach is the tractographic analysis in corticothalamic connections of PD.…”
Section: Dti Changes In Dopaminergic Tractsmentioning
confidence: 99%
“…Using voxel-based analysis, two studies (90,148) found PD is associated with abnormal diffusivity in white matter tracts adjacent to the olfactory sulcus. Although tractography of the olfactory tract is practically difficult in this area, using ROI drawing, some studies (92,119,122) reported low FA of the olfactory tract in PD. Another interesting approach is the tractographic analysis in corticothalamic connections of PD.…”
Section: Dti Changes In Dopaminergic Tractsmentioning
confidence: 99%
“…Parkinson disease is often associated with olfactory dysfunction, and impaired sense of smell is one of the earliest clinical symptoms of PD, preceding even the classic motor signs (104). Using ROI analysis, significant group differences in FA and MD have been observed in the anterior olfactory structures (33). These results were confirmed by Rolheiser et al (49), who leveraged TBSS to reveal significant group differences between PD and controls in the anterior olfactory region, as well as the SN.…”
Section: Dti In Early-stage Pdmentioning
confidence: 80%
“…First, it has been shown by Ibarretxe-Bilbao et al that FA values in the olfactory tract differ between early-stage PD patients and controls [ 51 ]. Second, studies by Rolheiser et al [ 52 ] and Joshi et al [ 53 ] further showed that the DTI signals of olfactory regions could better differentiate early-stage PD patients from healthy controls, as compared with signals from the substantia nigra.…”
Section: Methodsmentioning
confidence: 99%